Trade, Industrial Dissimilarity, FDI and Business Cycle Co-movements: EC3SLS Evidence from Eurozone Economies. (August 2019) - Kunroo, Mohd Hussain
This article uses simultaneous equations error component three-stage least squares (EC3SLS) panel data technique to find the direct and indirect impacts of trade, industrial dissimilarity and FDI on the business cycle synchronisation of Eurozone economies. The period of analysis is 1990–2009. These are the major findings: (a) trade, industrial dissimilarity and FDI have both direct and indirect effects on the business cycle synchronisation of sample economies; (b) EC3SLS estimates show that closer trade ties among these Eurozone countries have led to more synchronised business cycle co-movements, because common disturbances are more prevalent and intra-industry trade dominates; (c) the bilateral FDI flows have served as a source of destabilisation rather than a source of synchronisation; (d) industry-specific shocks have almost lost their importance both in terms of generating more trade and in terms of raising the output correlation of sample countries; (e) trade intensity and FDI flows are positively and significantly correlated, thereby suggesting that more FDI encourages more trade and vice-versa; (f) trade shows a negative relationship with industrial dissimilarity, which implies that bilateral trade in these countries promotes similar industrial structures; and finally, (g) these economies characterise intra-industry trade patterns, as expected in the case of these highly integrated Eurozone economies. Although the results show the presence of intra-industry trade types, these economies have diversified their production processes at the higher income levels. JEL: E32, F02, F10, F11, F15, C33